PENGARUH HARGA DAN KUALITAS PRODUK PAKET INTERNET TERHADAP KEPUTUSAN PEMBELIAN KARTU PRABAYAR SIMPATI (STUDI KASUS PADA MAHASIWA PROGRAM STUDI MANAJEMEN UNIVERSITAS SJAKHYAKIRTI PALEMBANG) - Tutik Pebrianti (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
This study aims to determine: (1) The effect of internet package prices on the decision to purchase a prepaid sympathy card. (2) To determine the effect of internet package product quality on the decision to purchase a prepaid sympathy card. The sample used in this study were students and students of the Management Study Program, Sjakhyakirti University, Palembang. As for the number of respondents as many as 154 respondents, the data was obtained through a questionnaire while the method used in this method sampling was the incidental sampling. The analytical method used is a quantitative method. The analysis technique used in analysis Partial Least Square (PLS) with the help of the SmartPLS version 3. The results of testing the hypothesis show that the variables: (1) the price variable has a significant effect on the purchasing decision variable, as indicated by the t-count value is 2.703, then 2.703 >1 .97 This indicates that the t count is greater than the t table, then with a p value of 0.007, it is found that 0.007 <0.05. (2) The product quality variable has a significant effect on the purchasing decision variable, as indicated by the t-count value is 5.644, then 5.644>1.97. This indicates that the t-count is greater than t-table, with a p value of 0.000, then 0.000 <0.05.